Intercanine distance in children with temporary, mixed and permanent dentition - Yenis Alfonso Díaz; Gudelia Alemán Estévez; Isabel Martínez Brito (Editorial Ciencias Médicas, 2019)
Introduction: Intercanine distance values are a useful auxiliary reference to predict space deficiency problems related to transverse maxillary growth. Objective: Determine intercanine distance values for children with normal occlusion in both dental arches during the different dentition periods. Methods: A descriptive, cross-sectional study was conducted. The study universe was 6 033 schoolchildren, from whom a stratified random sample was selected of 525 children aged 3, 6, 9 and 12 years, corresponding to the stages of dental development: temporary, early mixed, late mixed and permanent dentition. Facial and oral clinical examination was performed, based on the inclusion criteria. The variables studied were age, sex, upper intercanine distance and lower intercanine distance. The possible association between intercanine distance and sex and age was determined with Student's independent samples t-test and analysis of variance (ANOVA), respectively. Results: Upper intercanine distance was 27.3 mm at 3 years, 30.42 mm at 6 years, 31.67 mm at 9 years and 32.93 mm at 12 years. Lower intercanine distance was 23.19 mm, 24.66 mm, 25.61 mm and 25,98 mm at 3, 6, 9 and 12 years, respectively. Male subjects exhibited greater values. Significant differences were found with respect to sex in upper intercanine distance at 6 and 12 years (p= 0.000) and in lower intercanine distance at the same ages (p= 0.001 and p=0.01), as well as in upper and lower intercanine distance across the different ages (p= 0.000). Conclusions: Intercanine distance increases in both jaws with age. A predominance was found of a greater width in the male sex in both jaws at 6 and 12 years of age.